2006
DOI: 10.1055/s-2006-924734
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Canavan Disease Revealed by Proton Magnetic Resonance Spectroscopy (1H‐MRS) and Diffusion-weighted MRI

Abstract: Canavan disease is a childhood leukodystrophy caused by mutations in the gene for human aspartoacylase ( ASPA), which leads to an abnormal accumulation of the substrate molecule N-acetyl-aspartate (NAA) in the brain. This study was designed to model the natural history of Canavan disease using MRI and proton magnetic resonance spectroscopy ( (1)H-MRS). NAA and various indices of brain structure (morphology, quantitative T1, fractional anisotropy, apparent diffusion coefficient) were measured in white and gray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 47 publications
0
63
0
Order By: Relevance
“…In addition to causing accumulation of NAA in brain and other tissues, loss of ASPA activity leads to spongy degeneration of white matter associated with progressive loss of myelin [3,4]. Animal models with inactivated ASPA have proved useful in the study of this condition, as with the knockout mouse that was shown to have morphologically abnormal myelin [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to causing accumulation of NAA in brain and other tissues, loss of ASPA activity leads to spongy degeneration of white matter associated with progressive loss of myelin [3,4]. Animal models with inactivated ASPA have proved useful in the study of this condition, as with the knockout mouse that was shown to have morphologically abnormal myelin [5].…”
Section: Discussionmentioning
confidence: 99%
“…The genetic defect in these animals involves deletion of the aspartoacylase (ASPA; N-acetyl-L-aspartate amidohydrolase) gene, a feature that has made it a naturally occurring model of Canavan disease. This autosomal recessive childhood disorder is characterized by CNS swelling and spongy degeneration of white matter, along with accumulation of N-acetylaspartate (NAA) in brain and urine [3,4]. White matter pathology in rodent models, such as the ASPA-null knockout mouse, was shown to involve myelin vacuolization as a feature of dysmyelination and/or demyelination [5].…”
Section: Introductionmentioning
confidence: 99%
“…The physiological role of ASPA is to hydrolyse N-acetyl-L-aspartic acid (NAA), producing (e.g. in oligodendrocytes) Laspartic acid (Asp) and acetate (Ac) (see Figure 1 for more details); as expected, its deficiency leads to abnormally high central nervous system (CNS) NAA levels (>35%) (Janson et al, 2006b), with vast amounts of NAA being excreted in urine (N-acetylaspartic aciduria). It should be noted that urinary NAA levels are 10-100 fold higher in CD patients than age-matched healthy subjects, and this is the preferred method of CD diagnosis (Hagenfeldt, 1987).…”
Section: Introductionmentioning
confidence: 89%
“…(13,14). Their MRI shows diffuse involvement of white matter including the subcortical U fibers (15). There is also involvement of basal ganglia and other gray matter structures.…”
Section: Conventional Brain Mri Lesion Patterns In Ldmentioning
confidence: 99%